Pengaruh Kegiatan Outward Bound terhadap Hasil Pembelajaran dan Profil Disiplin Mahasiswa FPOK UPI - Suhendra, Dede Iman (Jurnal Keolahragaan, 2023)
This study aims to evaluate the learning outcomes and discipline profiles of students from the Faculty of Sports and Health Education (FPOK UPI) who participated in Outward Bound activities. Using a quantitative descriptive method and survey techniques, data were collected from 30 students across three study programs through Likert-scale questionnaires and academic records. The results show that most students achieved Grade Point Averages (GPA) in the "satisfactory" to "very satisfactory" categories and demonstrated high levels of discipline. The Outward Bound program positively contributed to both academic achievement and character development, particularly in fostering discipline, responsibility, and teamwork. These findings support the integration of Outward Bound into higher education character-building programs as an effective experiential learning strategy.